Ozone therapy in veterinary medicine – Literature review - Botacini, Sofia de Barros; Silva, Maria Eduarda Cruz e; Ferraz, Milena Lopez; Cunha, Isabelle Aiello Teixeira da; Prado, João Ricardo; Meneguelli, Mariana; Munaretti, Beatriz dos Santos; Fachini, Charles Alexandre Mendonça; Silva, Letícia Peternelli da; Costa, Isabela Bazzo da (Seven Editora, 2024)
Ozone, in addition to being present in the stratosphere and contributing to the filtration of ultraviolet rays, has been studied for its use in medicinal purposes. This gas has high oxidizing power, bactericidal, fungicidal and viricidal properties. The application of medical ozone is among the most promising due to its low investment and maintenance costs, ease of application and clinical results. The objective of this study was to report and inform the efficiency of ozone therapy as an alternative protocol for several diseases in veterinary care. DOI:https://doi.org/10.56238/sevened2024.007-067